Развитие познавательной активности одаренных детей в условиях реализации социально-педагогической поддержки - Турлубаева, Д.К. (My University, 2013)
The article deals with the development of cognitive activity of gifted children in the imple- mentation of social and pedagogical support with the use of innovative approaches and pedagogical technology in the learning process.